2015
DOI: 10.1128/jvi.03330-14
|View full text |Cite
|
Sign up to set email alerts
|

N -Linked Glycosylation Protects Gammaretroviruses against Deamination by APOBEC3 Proteins

Abstract: Retroviruses are pathogens with rapid infection cycles that can be a source of disease, genome instability, and tumor development in their hosts. Host intrinsic restriction factors, such as APOBEC3 (A3) proteins, are constitutively expressed and dedicated to interfering with the replication cycle of retroviruses. To survive, propagate, and persist, retroviruses must counteract these restriction factors, often by way of virus genome-encoded accessory proteins. Glycosylated Gag, also called glycosylated Pr80 Gag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Among the functions that have been attributed to glycogag is protection of MLVs against restriction by mA3 (7, 10, 30, 31). We have tested for this activity in our experimental system.…”
Section: Resultsmentioning
confidence: 99%
“…Among the functions that have been attributed to glycogag is protection of MLVs against restriction by mA3 (7, 10, 30, 31). We have tested for this activity in our experimental system.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, glyco-Gag-defective viruses reverted to wild-type function during infections of A3-expressing animals, but not A3-null animals, demonstrating the importance of glyco-Gag in antagonizing A3-dependent restriction (Stavrou et al, 2013). Recent data have also indicated that loss of N-linked glycosylation sites in glyco-Gag result in increased hypermutation by A3 (Rosales Gerpe et al, 2015). Interestingly, glyco-Gag-mutant virions are less stable than wild-type particles during ultracentrifugation with detergent (Stavrou et al, 2013).…”
Section: Retrovirus Restriction By Murine A3 – In Vivo Insights From mentioning
confidence: 99%
“…Vifs directly bind A3s often in a species-specific manner and recruit them to an E3 ubiquitin ligase complex containing Cullin5 (Cul5), elongin B/C (EloB/C), and RING-box protein RBX2 to induce polyubiquitination and degradation of the A3s by the proteasome (17,18). Other retroviral proteins that counteract A3s are Bet of foamy viruses, the nucleocapsid of human T cell leukemia virus type 1 and the glycosylated (glyco)-Gag of murine leukemia virus (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Primates have seven genes (A3A to A3D, A3F to A3H), whereas cats encode four genes (A3Z2a to A3Z2c, A3Z3) (3)(4)(5). A3 proteins contain either one or two zinc (Z)-binding domains with the conserved motif of HxE(x) [23][24][25][26][27][28] CxxC (where "x" can be any residue) (4). These proteins can target retroviruses and inhibit viral replication by deamination of cytidines in viral single-strand DNA that forms during reverse transcription, introducing G-to-A hypermutations in the coding strand (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%